Perancangan Video Tutorial “Mechanic Shift Salesforce” United Tractors Bagi Mekanik Dan User - Aria Befrima Daffa; Heldi Heldi (Lembaga Pengembangan Kinerja Dosen, 2023)
Optimization of video tutorial information media in the world of work is needed for mechanics and users at United Tractors, because it can have an impact and contribution to United Tractors, but because their performance is not optimal, a solution is needed to solve this problem. The purpose of this design is to create information media for the